Assessing climate change impacts on heat waves and heat index: a case study of Uttar Pradesh, India - Awasthi, Amit; Dutta, Arindam; Pathak, Vinayak Vandan; Kaur, Simranjeet; Kumar, Vajinder; Lodh, Abhishek (Frontiers in Climate, 2026)
Extreme environmental events such as Heat Waves (HWs), cold waves, and droughts intensified by climate change are increasingly associated with adverse health outcomes. In this study, investigation of the extreme temperature across Uttar Pradesh (U. P.), one of India’s largest and densely populate states has been done. Using high-resolution climate data from the Providing REgional Climates for Impacts Studies (PRECIS) model, including maximum temperature (Tmax), minimum temperature (Tmin), and Relative Humidity (RH) were systematically extracted for different districts of U. P. Heat Index (HI) and HW were then calculated for three distinct periods: 1961–1990 (base century), 2021–2050 (mid-century), 2071–2098 (end-century), respectively under the A1B scenario. Results show a clear intensification of extreme temperature conditions, with several districts expected to experience extensive, more frequent, and more severe HW and HI events in future climate scenarios. Based on HI, it is observed that nearly all districts of U. P. are likely to end up in the danger zone especially during May and June months. Districts like Gazipur, Jaunpur, Varanasi, and Chandauli are more impacted by heat as they show higher HI values, a greater number of HW days, and stronger deviations in temperature extremes, which together indicate growing risks of extreme thermal discomfort. The intended audience for this research includes climate scientists, public health authorities, disaster-risk planners, and local government agencies. Researchers working on regional climate impacts can apply these insights to strengthen future heat-risk assessments. Overall, this study provides a scientific foundation for targeted heat-risk mitigation in U. P. and emphasizes the urgent need for localized adaptation strategies to safeguard communities against intensifying extreme heat. These findings also contribute to the global understanding of extreme heat resilience in a warming world.